Agriculture, structural transformation and poverty reduction: Eight new insights - Christiaensen, Luc; Martin, Will (Elsevier, 2018)
Whether the sector of growth matters for the speed of poverty reduction, why, and how best to invest to maximize the poverty reducing effects of sectoral growth remain topics of intense debate. Drawing on the more recent history and applying a range of methods, the papers in this special issue confirm the view that growth in agriculture is on average more poverty reducing than an equivalent amount of growth outside agriculture. They also add important nuances to this broad empirical regularity, uncover a series of structural conditions that affect this relation, and show that different mechanisms to finance public investment to boost sectoral growth (deficit financing, taxation or aid) can have widely different impacts on poverty, a widely-ignored issue so far. They do so by going beyond the traditional agriculture-nonagriculture dichotomy, also looking at the subsectors and the differential effects of prices versus productivity. They further distinguish between production for home and market consumption, between modern, outward oriented and informal domestically - focused firms, as well as between secondary towns and cities. Eight key insights emerge.